State-of-the-art infrared detector technology - Kinch, Michael A. (SPIE Press monograph, 2014)
Scientists, engineers, managers, and policy makers who are currently involved in the funding of infrared R&D and subsequent system design and manufacture are confronted with a choice between two competing materials technologies, HgCdTe and III-V alloys. This book examines both the current and future performance of infrared focal plane arrays that use the various device architectures associated with these two materials technologies. All spectral bands from long wavelength (LWIR) through mid-wavelength (MWIR) to short wavelength (SWIR) are considered, ultimately with a view to achieving background and diffraction-limited system performance at room temperature for all wavelengths